Keselamatan Dalam Konsep Rasul Paulus - Susanti, Aya (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
Salvation in the concept of the Apostle Paul is very worthy to be studied considering the Apostle Paul wrote the most books in the New Testament. In addition, the concept of salvation is a primary doctrine that becomes a dogmatic grip for the church of God. The author conducted a literature study from several relevant sources to discuss this topic. The author examines the view of salvation in general from the letter of the Apostle Paul and then ends more specifically according to Romans. The general letters written by Paul and especially the Romans indicate the Apostle Paul's concept of salvation is theomorphistic, departing from God, by God and for God. The concept is also in harmony with the contents of the Gospels and other books throughout the Bible